Human Resources Management: Current Issues - Anton Florijan Barišić; Igor Klopotan; Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Human resources management (HRM) as a function providing organizations with workforce and thus assisting the achievement of organization's business strategy is an inevitable element of contemporary organisation's arrangements. Passing through different stages from conventional one to strategic service, HRM has transformed its concept, content, philosophy and scope of services affecting the way of understanding and role of the HR function in the organization. Becoming one among most important organizational functions, HRM was transiting from reactive function, over independent function towards the integrative and supportive function. This paper is aimed in contributing to the better understanding of contemporary challenges of HRM function and HR services in organizations, analysing various concepts and describing development and nature of different aspects and recent approaches to the HRM in terms of their influence to achieving and maintenance of organizational business strategy and competitive advantage. In that sense, the objective of the paper is to provide the overview of HRM contemporary challenges, and assess its impact to modern organization in context of organizational performance and organizational effectiveness.
Keywords: M10; M12; O32; L22; L25; M55; 330; management; human resources; human resources management; organisation; organisational performance; organizational effectiveness; digital transformation; aging workforce